Persepsi Dosen dalam Menerapkan Kurikulum Inovatif - Huda, Hisbullah; Baihaqi, M.; Fathoni, Fathoni (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
Purpose- This paper aims to describe lecturers' perceptions of university readiness in implementing an innovative curriculum at UIN Sunan Ampel Surabaya, and lecturers' readiness to face the challenges of curriculum implementation related to the development of students' soft skills and hard skills. Design/Methodology/Approach- This type of research is descriptive quantitative research.  The subjects of this study were lecturers of the Arabic Language Education Study Program in the 4th semester of the 2022-2023 academic year. The number of lecturers in the Arabic Language Education Study Program at UIN Sunan Ampel Surabaya is 13 lecturers. To obtain data about their perceptions, questionnaires, interviews and documentation were used. To analyze the data that has been obtained, tendency analysis is used. Findings- The results of this study indicate that the lecturers' perceptions that the University is ready to implement an innovative curriculum called MBKM in the Arabic Language Education Study Program at UIN Sunan Ampel Surabaya show a very good level. The readiness of lecturers to implement an innovative curriculum in the Arabic Language Education Study Program at UIN Sunan Ampel Surabaya shows a good level and even tends to be very good, this is shown in the lecturers' understanding of the innovative curriculum, and also their skills to help improve students' soft skills and hard skills.